2016
DOI: 10.1136/bmjopen-2016-011643
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory distress syndrome in moderately late and late preterm infants and risk of cerebral palsy: a population-based cohort study

Abstract: ObjectivesInfant respiratory distress syndrome (IRDS) is a known risk factor for intracerebral haemorrhage/intraventricular haemorrhage (ICH/IVH) and periventricular leucomalacia. These lesions are known to increase the risk of cerebral palsy (CP). Thus, we wanted to examine the long-term risk of CP following IRDS in moderately late and late preterm infants.DesignPopulation-based cohort study.SettingAll hospitals in Denmark.ParticipantsWe used nationwide medical registries to identify a cohort of all moderatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Not all of this increase in adverse perinatal outcomes is related to the cause of the preterm birth rather than the prematurity itself [2]. Respiratory complications, especially, appear to relate more directly to prematurity regardless of the underlying cause and, importantly, those neonates suffering respiratory distress syndrome are at greater risk of long-term neurodevelopmental morbidity than are those without [3,4]…”
Section: Short-term Outcomesmentioning
confidence: 99%
“…Not all of this increase in adverse perinatal outcomes is related to the cause of the preterm birth rather than the prematurity itself [2]. Respiratory complications, especially, appear to relate more directly to prematurity regardless of the underlying cause and, importantly, those neonates suffering respiratory distress syndrome are at greater risk of long-term neurodevelopmental morbidity than are those without [3,4]…”
Section: Short-term Outcomesmentioning
confidence: 99%
“…All preterm infants are at risk for re-hospitalization, as well as medical and neurodevelopmental complications, even moderate to late preterm infants (born at 32 to <37 weeks’ gestation) [ 6 ]. A particularly challenged sub-group is very low birth weight (VLBW) infants or those born < 1500 g. More than 90% of VLBW infants are discharged home from the neonatal intensive care unit (NICU).…”
Section: Introductionmentioning
confidence: 99%
“…The Danish Medical Birth Registry Cohort showed that the incidence of RDS in infants born at 32–36 weeks of gestation was approximately 5.7%. 26 In the same study, the incidence of intracranial or IVH was 2.0% and of PDA was 3.4% in the RDS group. In our study, the incidence of IVH or PDA is higher than previous study, it is necessary to take careful consideration for preventing complication among the late preterm infants.…”
Section: Discussionmentioning
confidence: 78%